(untitled) (Journal of Fiber Bioengineering and Informatics, 2014)
In this research, a mathematic model for predicting the average pressure at the lower leg caused by socks has been built. This research establishes a relationship between the average pressure of socks, the potential energy of fabrics and the shape of the lower leg section based on the law of conservation of energy. On the basis of the result, the mathematic model has also been built up to predict average pressure, and the model was proved by both the data of experiments and the relation between the average pressure, the shape of the lower leg section and the elastic potential energy of the fabrics. The results has shown that the average pressure caused by the socks at the lower leg is related to the circumference of the welt as well as the circumference of calf and elasticity of the welt. The testing result shows that this model can be used to predict the pressure. This model will simplify the calculation method, and provide a theoretical foundation for the accurate prediction of the pressure at any given positions.